MediGuard: Telegram-Based Smart Medication Reminder System with Multi-Stage Alert Mechanism and Voice Notification - Tsanaiya Zuhura; Vania Rapita Augesta; Djuniadi Djuniadi; Abdurrakhman Hamid Al-Azhari (Department of Electrical Engineering, UNJANI, 2026)
Medication non-adherence among elderly patients remains a critical healthcare challenge, with 40-60% failing to take prescribed medications at correct times. Existing reminder systems often require proprietary mobile applications, subscription-based IoT platforms, or costly GSM infrastructure, creating barriers to widespread adoption. This paper presents MediGuard, a cost-effective medication reminder system leveraging Telegram Bot API for universal accessibility without custom application requirements. The system employs a dual-microcontroller architecture: ESP32 manages WiFi communication, schedule storage via SPIFFS, and implements a novel four-stage progressive alert mechanism (LED activation, waiting period, blinking pattern, final timeout), while Arduino Nano handles integrated health monitoring through MAX30102 pulse oximeter, DHT11 environmental sensor, and MQ-2 smoke detector. A key innovation is the incorporation of ISD1820 voice module enabling personalized audio reminders superior to conventional buzzer alerts. User interaction occurs entirely through familiar Telegram commands (/add, /list, /clear), eliminating installation barriers. System testing demonstrates <3-second schedule accuracy, 50ms voice trigger latency, and reliable operation over extended periods. This approach achieves significant cost reduction compared to GSM-based solutions while maintaining scalability and user-friendliness suitable for elderly populations.